PENERAPAN RANCANGAN BLOK RANDOM TIDAK LENGKAP SEIMBANG PADA KOMBINASI PUPUK NANOSILIKA DAN PUPUK NPK TERHADAP PERTUMBUHAN TANAMAN JAGUNG - Asismarta, Asismarta; Suparti, Suparti; Sudarno, Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Balanced Incomplete Block Design (BIBD) when all treatment comparisons are equally important, the treatment combinations used in each block should be selected in a balanced manner so that any pair of treatments occur together the same number of times as any other pair. The data used is the result a simulation of the generation of data using program packages MINITAB 16 that normal distributing with a and varying Based on the study of cases the combined effect fertilizer nanosil and fertilizer NPK on the growth of corn plant, tested on 6 treatment and 10 block with every treatment repeated as many as 5 times and each block unfilled 3 treatment. Assuming model that is residual the normal distribution, independence and variant homogeneous. When third this assumption be accepted then followed the effect treatment (adjusted) against an observed, when having effect and undergone a further Tukey to know treat which that differ significantly. Of treatment to be adjusted obtained with combination 25% fertilizer nanosil + 75% fertilizer NPK who gives the average the biggest contributor to the growth of plants corn.Keywords : BIBD, Tuckey test, normality, independence, equal variance